(untitled) (Archaeologia Adriatica, 2017)
Two hoards of Late Antiquity coins from Zadar’s surroundings are catalogued in this paper. The first one includes 9 coins found in an amphora on the seabed near the island of Olib in 1962, dated to the period spanning the reigns of Tacitus and Constantius I. The second hoard is made up of 27 coins from the period of Constantine I and his sons; it was found at the “Travnjaci” site in Radovin in 1963, but the detailed context of the find is not known. The two hoards are similar due to the fact that they contain coins from a very short period of time. The Radovin hoard also includes two unusual Constantine coins minted in Ticino, one of which has an irregular reverse and the other has a subsequently imprinted mark above the laureate portrait. Terminus ante quem for the Olib hoard is 296 AD and for the Radovin hoard somewhat after September 326 AD.